2016
DOI: 10.1111/jgh.13256
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori vacuolating cytotoxin genotypes and preneoplastic lesions or gastric cancer risk: a meta‐analysis

Abstract: The H. pylori vacA-s1 and vacA-m1 allelic variants strongly increased susceptibility to IM and GC; however, only s1 showed an association with AG. These associations were largely influenced by geographic variations in the GC incidence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…Fifteen studies in the meta-analysis (1) confirmed the association of the s1m1 genotype with an increased risk for gastric cancer, however studies from Belgian and India only confirmed an association with vacA s1 but not with m1 (8,9). In Thailand (10), s, m or s, m, combination showed no statistically significant association with clinical outcome.…”
Section: Consistencymentioning
confidence: 94%
See 3 more Smart Citations
“…Fifteen studies in the meta-analysis (1) confirmed the association of the s1m1 genotype with an increased risk for gastric cancer, however studies from Belgian and India only confirmed an association with vacA s1 but not with m1 (8,9). In Thailand (10), s, m or s, m, combination showed no statistically significant association with clinical outcome.…”
Section: Consistencymentioning
confidence: 94%
“…Although there are no value that clearly separates “strong” from “moderate” or “weak” associations, RR values below three are considered moderate or weak (7). The Abdi et al meta-analysis (1) reported relatively weak associations (i.e., RR's below 1.5) for both s1 and m1 and for the combination of s1m1.…”
Section: Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 The production of vacuolating cytotoxin (VacA), encoded by the vacA gene, is another important virulence factor used by H. pylori to induce cytoplasmic vacuolization in gastric cells. 7,8 Once internalized, VacA induces cytochrome C release from mitochondria, promoting apoptosis. Moreover, VacA binds to the cellular epithelium by interacting with tyrosine phosphatase proteins and enhancing pore formation in cell membranes.…”
mentioning
confidence: 99%